A decent roof for the poor - a Malaysian perspective. - Syed Junid, Syed Mansur (1987)
Malaysia has embarked on a very objective project of providing 80,000 units low cost houses every year for the next three years. This announcement made by the government last year was very well applauded by the building sectors as well as the housing developers. This paper looks at this special low cost housing programme and its progress. It also looks at some of the research work being conducted in the country in trying to provide a 'decent roof for the poor'. Research on oil palm fibre cement roof tiles, bamboo, lighweight concrete, rubber wood trusses and ferrocement panels for application to low-cost housing to reduce the costs further were also highlighted.